Direct access to multi-functionalized benzenes via [4 + 2] annulation of α-cyano-β-methylenones and α, β-unsaturated aldehydes. Issue 49 (6th August 2020) - Jia, Qianfa; Lan, Yunfei; Ye, Xin; Lin, Yinhe; Ren, Qiao
Abstract : An efficient [4 + 2] benzannulation of α-cyano-β-methylenones and α, β-unsaturated aldehydes was achieved under metal-free reaction conditions selectively delivering a wide range of polyfunctional benzenes in high yields respectively (up to 94% yield). Abstract : An efficient [4 + 2] benzannulation of α-cyano-β-methylenones and α, β-unsaturated aldehydes was achieved under metal-free reaction conditions selectively delivering a wide range of polyfunctional benzenes in high yields respectively (up to 94% yield).